Build it and they will cycle: Causal evidence from the downtown Vancouver Comox Greenway. (May 2021) - Frank, Lawrence D.; Hong, Andy; Ngo, Victor Douglas
Abstract: This study evaluated changes in cycling trips before and after the construction of an urban greenway in Vancouver, Canada. Urban cycling has gained in popularity as a healthy and environmentally friendly mode of transport. Carsharing is also on the rise globally, and it has the potential to disrupt urban mobility, including cycling and public transit. In this study, we hypothesized that cycling trips will increase after the opening of the greenway for residents living within 300 meters of the greenway compared to those living further away. We also posited that carsharing membership would have a positive impact on cycling uptake. Data were drawn from a three-year natural experiment study (2012–2015) of the Comox-Helmcken Greenway ("Comox Greenway") in Vancouver. An experimental-and-control design was employed to compare pre-post differences in cycling trips for residents within 300 m of the greenway (experimental group, n = 239) and those further away (control group, n = 285). The opening of the greenway resulted in a 251% increase in cycling trips for the experimental group compared to the control group. Ethnically white subjects reported 130% more cycling trips than non-white subjects, and those aged 65 and older reported 79% fewer cycling trips than younger age cohorts. Carshare membership reduced the number of cycling trips after the greenway opening. Results suggest that greenways could be an effective strategy to boost urban cycling, and that carsharing programs may have a countervailing effect on cycling. The findings support recent initiatives to reappropriate road space in urban areas for cycling and walking due to the COVID-19 pandemic. Highlights: Findings support recent initiatives to reappropriate road space for cycling and walking due to in part to the pandemic. The construction of an urban greenway resulted in a considerable increase in biking for those living within 300 meters. Car sharing increases vehicle access and makes driving easier and may reduce cycling in highly walkable locations. Positive greenway impacts were disproportionately enjoyed by both white and younger participants.